Agro-industrial wastes as solid adsorbents for glycerol removal: Potential use in biodiesel dry purification - Munoz, Alejandra D.T.; Lucca, Guilherme de; Damasceno, Kelly G.; del Roveri, Carolina; Carvalho, Ana Karine F.; de Paula, Ariela V. [UNESP]; Andrade, Grazielle S.S. (Elsevier, 2024)
Biodiesel purification consumes significant amounts of potable water. Therefore, there is a need for novel dry purification technologies that are sustainable and low-cost. This study aimed to add value to agro-industrial wastes by exploring their potential as glycerol biosorbents for dry purification of biodiesel. The following agro-industrial biomasses were tested without chemical modification: banana peel (BP), coconut fiber (CF), coffee husk (CH), and sugarcane bagasse (SB). The biomasses were characterized for particle size, chemical composition, X-ray diffraction and surface area. In a preliminary experiment, adsorption efficiency was evaluated in a synthetic medium of glycerol solution. Except for BP, all biomasses were found to remove glycerol, achieving a mean removal of 42 %. The best biosorbent dosage was 10 mg/mL dry biomass. CF had the best glycerol removal and adsorption capacity at all dosages. A kinetic study revealed that the pseudo-second-order model provided the best fit to experimental data. An isotherm study indicated that different models were well suited to explain the mechanism of glycerol adsorption on CF. When applied in methyl and ethyl biodiesel produced from soybean oil by homogeneous basic catalysis, coconut fiber removed 67 % and 70 % of residual glycerol, respectively. The results indicate that coconut fiber holds great potential as a glycerol adsorbent in purification processes.
Keywords: Adsorption; Biodiesel; Coconut fiber; Dry purification; Glycerol